2021
DOI: 10.1111/psyg.12688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of financial incentives for participation in dementia prevention and support activities: results of a web survey with persons aged 60 and older

Abstract: Background This study aims to elucidate the impact of financial incentives on the motivation to participate in dementia prevention activities and to provide support to people with dementia. Methods An online survey was completed by 1500 men and women, aged 60 or above, from the general community in Japan. When responding to questions regarding motivation for participating in dementia prevention activities and providing support to people with dementia, respondents were randomly assigned different incentive cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The remaining 521 articles underwent a full-text evaluation to determine eligibility. Finally, 46 RCTs [ 3 , 4 , 12 55 ] met the criteria for final inclusion in our systematic review and meta-analysis. The process of study selection and the reasons for exclusion are shown in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 521 articles underwent a full-text evaluation to determine eligibility. Finally, 46 RCTs [ 3 , 4 , 12 55 ] met the criteria for final inclusion in our systematic review and meta-analysis. The process of study selection and the reasons for exclusion are shown in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Attrition bias was a high risk of bias in three RCTs [ 33 , 35 , 41 ], unclear risk of bias in Boucher et al [ 14 ], and low risk of bias in the rest of the included RCTs. Selective reporting was low risk in all included RCTs, except three RCTs were at high risk of bias [ 4 , 28 , 35 ]. The risk of bias summary for each study and the risk of bias graph for bias domains is shown in Fig 2 and S1 Fig .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations